Térey hagyományai: Stílusimitáció, nemzedéki élmény és önéletrajziság Térey János prózájában - Radnai, Dániel Szabolcs (Studia Litteraria, 2022)
This paper discusses the prose volumes of János Térey, focusing on the importance of style imitation, autobiography and generational experiences in Termann hagyományai (“Termann’s traditions”, 1997) and the re-written version of the volume entitled Termann hagyatéka (“Termann’s testament”, 2012). The purpose of my investigation is to show that there is a connection between Térey’s poetical traditions (sentimentalism, aesthetic modernism), the genre of the volumes (short story cycle) and the (auto)biographical narrative presented in the Termann cycle and, to a lesser extent, in his posthumous memoir (Boldogh-ház, Kétmalom utca [Boldogh House, Kétmalom Street], 2020). The thesis of the paper is that Térey adjusted his first prose volume to his later poetic oeuvre by the poetical reworking of the Termann-texts and by reducing the significance of the autobiographical and generational aspects that had originally played a crucial role in them. ¤e article addresses the relevance of Térey’s rewriting aspirations in the context of his generation and the atmosphere of the contemporary Hungarian literary scene, comparing his career to that of his contemporaries (Krisztián Peer, Zoltán Poós).